Histology for pathologists - Mills, Stacey E. (Wolters Kluwer, 2020)
"The fourth edition of Histology for Pathologists was published in 2012 and, as before, it is again reasonable to ask if "normal" has changed enough in the ensuing 6 years to justify a new edition. The answer, of course, is that normal has not changed at all (evolution is indeed a slow process!) but our perception of normal continues to expand and improve. In particular, we have developed many new immunohistochemical markers, and the ever-growing spectrum of their expression in normal tissues provides insights into pathologic processes arising from or differentiating toward these tissues. We also continue to recognize new variations of normal that cause diagnostic confusion and touch on the interface between normal and disease. Accordingly, the fifth edition brings incremental but valuable improvements in our perceptions of human histology"--Provided by publisher